2022
DOI: 10.1139/tcsme-2020-0149
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic mode decomposition of elliptical liquid jets in crossflow

Abstract: Dynamics of round and elliptical liquid jets in subsonic crossflow is studied using high-speed imaging technique. The experiments are performed at constant gaseous weber number and liquid-gas momentum flux ratio of 6.45 and 17.87 respectively, with orifices of different aspect ratios having an equivalent diameter of 0.43 mm. All cases are carried out inside an open loop subsonic wind tunnel with a test section of 100*100*750 mm. For each case, dynamic modes are generated directly from the snapshots using a var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Results showed that the penetration depth increased and the droplet size decreased with bigger injection angles. Mokhtarpour et al 22 and Zhou et al 23 both analyzed the cases of elliptical jet and cylindrical jet in air crossflow. The elliptical jet broke up earlier, and with a lower penetration depth, making the atomization even more difficult.…”
Section: B Mixing Enhancement Schemesmentioning
confidence: 99%
“…Results showed that the penetration depth increased and the droplet size decreased with bigger injection angles. Mokhtarpour et al 22 and Zhou et al 23 both analyzed the cases of elliptical jet and cylindrical jet in air crossflow. The elliptical jet broke up earlier, and with a lower penetration depth, making the atomization even more difficult.…”
Section: B Mixing Enhancement Schemesmentioning
confidence: 99%